A study on the relationship between knowledge management and the impact towards organizational performance of Perbadanan Kemajuan Negeri Melaka / Nurul Shahirah Ishak - Ishak, Nurul Shahirah (2011)
Perbadanan Kemajuan Negeri Melaka is one of the organizations who are responsible for Melaka development. The State Economic Development Corporation (PKNM) was established under the State Economic Development Corporation Melaka. Enactment No 1, 1971 and was given the role and main task to develop the state of Melaka into four main areas namely Industrial, Tourism, Housing, Business and Commerce. In giving best presentation to customers, they should have a ‘pleasant personality’ from internal. Therefore, knowledge management plays important roles in giving the good result to others. Knowledge management can be measure in terms of knowledge on technology, organizational culture, organizational structure, acquisition, conversion, application and protection. So, the purpose of this research is to identify the relationship between knowledge management and to see the impact towards organizational performance. Perbadanan Kemajuan Negeri Melaka staff becomes respondents for this research paper. 50 respondents were selected randomly from 6 departments. Beside, researcher also comes out with the recommendation which she believe Perbadanan Kemajuan Negeri Melaka may take it as the opportunity to increase their organizational performance.